1963
DOI: 10.1002/jsfa.2740140309
|View full text |Cite
|
Sign up to set email alerts
|

Potassium‐magnesium antagonism in soils and crops

Abstract: After a general review of the most important antagonisms between magnesium and other cations, some special results from intensive pot experiments concerning the K/Mg antagonism are discussed. It is shown that it is only in soils absolutely deficient in Mg that the K/Mg antagonism has to be considered in respect to practical fertilisation. It is important to correct a deficiency in soil‐magnesium by application of magnesium fertiliser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1964
1964
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Interactive effects of K, Ca, and soil pH with plant Mg uptake have also been found in several earlier studies (Welte & Werner 1963;Salmon 1964;Christenson et al 1973), and various other workers have attempted to synthesise composite indices of several relevant soil properties. These attempts to improve predictions of plant Mg availability using soil data have led to the use of parameters such as percentage Mg saturation of cation exchange capacity or of total exchangeable bases (Alston 1972) and cation activity ratios of Mg, Ca, K, and H in equilibrium soil solution extracts (Bould 1964;Salmon 1964;Arnold 1967;Alston 1972).…”
Section: General Discussion and Conclusionmentioning
confidence: 58%
“…Interactive effects of K, Ca, and soil pH with plant Mg uptake have also been found in several earlier studies (Welte & Werner 1963;Salmon 1964;Christenson et al 1973), and various other workers have attempted to synthesise composite indices of several relevant soil properties. These attempts to improve predictions of plant Mg availability using soil data have led to the use of parameters such as percentage Mg saturation of cation exchange capacity or of total exchangeable bases (Alston 1972) and cation activity ratios of Mg, Ca, K, and H in equilibrium soil solution extracts (Bould 1964;Salmon 1964;Arnold 1967;Alston 1972).…”
Section: General Discussion and Conclusionmentioning
confidence: 58%
“…Significance of the latter approach is based on the ternary exchange between K-Ca-Mg especially in agricultural soils where these ions are dominating soil matrix (Romheld & Kirkby, 2010;Sparks et al, 1990). Ohno and Grunes (1985); Welte and Werner (1963);and Jakobsen (1992) conclusively demonstrated that either K, Ca or Mg deficiencies are not exclusively dependent on the soil solution concentration. Interactions between the ions also play a crucial role, and this relationship is commonly antagonistic in nature, hence quantifying these ions by accounting for these interactions is mechanistically justified.…”
Section: Discussionmentioning
confidence: 90%
“…Hypomagnesemia of primary origin is due to a dietary deficiency of Mg (Constable et al 2017). The concentration of Mg in the plant is partially determined by the level of exchangeable Mg in the soil (Metson 1974) and dietary Mg deficiency is associated with grasses in soils that have 0.2-0.3meq of exchangeable Mg/100g of plant roots (Welte & Werner 1963). The use of fertilizers with nitrogen (N), phosphorus (P) and potassium (K) reduces the exchangeable Mg in the soil and the availability of Mg for the plants and, consequently, for the animals (Kemp et al 1961, Grunes et al 1970, Fox & Piekielek 1984, Cohen et al 2004, Elliott 2008, Kumssa et al 2019.…”
Section: Introductionmentioning
confidence: 99%